2009
DOI: 10.1007/978-3-642-04342-0_1
|View full text |Cite
|
Sign up to set email alerts
|

Panacea: Automating Attack Classification for Anomaly-Based Network Intrusion Detection Systems

Abstract: Abstract. Anomaly-based intrusion detection systems are usually criticized because they lack a classification of attack, thus security teams have to manually inspect any raised alert to classify it. We present a new approach, Panacea, to automatically and systematically classify attacks detected by an anomaly-based network intrusion detection system. Keywords: attack classification, anomaly-based intrusion detection systems Today, security teams aim to automate the management of security events, both to optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 24 publications
0
19
0
1
Order By: Relevance
“…Bolzoni et al [2] claim that anomaly-based intrusion detection systems are often inefficient when it comes to classifying the attacks they detect. Therefore, security teams or administrators have to manually process each alert generated by the IDS.…”
Section: A Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Bolzoni et al [2] claim that anomaly-based intrusion detection systems are often inefficient when it comes to classifying the attacks they detect. Therefore, security teams or administrators have to manually process each alert generated by the IDS.…”
Section: A Backgroundmentioning
confidence: 99%
“…SVM is a set of supervised learning methods used for classification. SVM uses "support vectors" and "margins" to classify data into different groups and then assigns new data to a specific group based on distance (Bolzoni et al [2]). RIPPER is a rule induction algorithm that uses a set of IF-THEN rules.…”
Section: A Backgroundmentioning
confidence: 99%
“…Anomaly detection has been extensively leveraged in developing intrusion detection systems [7,19,22], where for instance Bolzoni et al [7] showed how to automatically and systematically classify detected attacks. The main idea was to compute similarities of the payloads of attack data, and later classify it automatically, semi-automatically, and even manually.…”
Section: Related Workmentioning
confidence: 99%
“…Panacea is heuristic-independent and supports user-defined attack classifications as well. This work appears in a refereed conference paper [3], which is joint work with S. Etalle and P.H. Hartel.…”
Section: Discussionmentioning
confidence: 99%